2003
DOI: 10.1021/ja035540l
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Irreversible Inhibitor Targeting a PDZ Protein Interaction Domain

Abstract: Irreversible inhibitors of proteases have proven themselves useful tools for determining which proteases are active under given conditions in tissues or cells and for studying the functional role that a protease plays in physiological processes. The application of such techniques to the study of the activity and function of protein-protein interactions has been hindered by the lack of guiding principles for the mechanistic design of irreversible inhibitors targeting the "active site" of a protein interaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 18 publications
0
60
0
Order By: Relevance
“…We confirmed that pretreatment with FJ9 for 30 min does not reduce the maximum signal intensity generated by the PDZ domain bound to Frz7 peptide. In addition, whereas the MAGI3 PDZ2 domain treated with the indole-3-carbinol compound shows a clear shift in mass spectrometry (29), the DVL3 PDZ domain exposed to FJ9 under identical conditions does not (data not shown). These data strongly suggest that FJ9 does not covalently bind to the DVL PDZ, at least within the period of observation.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We confirmed that pretreatment with FJ9 for 30 min does not reduce the maximum signal intensity generated by the PDZ domain bound to Frz7 peptide. In addition, whereas the MAGI3 PDZ2 domain treated with the indole-3-carbinol compound shows a clear shift in mass spectrometry (29), the DVL3 PDZ domain exposed to FJ9 under identical conditions does not (data not shown). These data strongly suggest that FJ9 does not covalently bind to the DVL PDZ, at least within the period of observation.…”
Section: Resultsmentioning
confidence: 90%
“…Our aim in this study was to design a proof-ofprinciple small-molecule inhibitor to block the interaction between the PDZ domain of DVL and the COOH-terminal region of Frz receptor and to test whether it inhibits down-stream Wnt signaling and suppresses cancer cell growth. We reported the structure-based design of an indole-3-carbinol compound that mimics the tetrapeptide sequence binding to a PDZ domain (29). This compound formed a covalent adduct by electrophilic alkylation of a histidine residue in the PDZ domain and therefore had limited therapeutic potential because electrophilic inhibitors often lack specificity in targeting biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few small-molecule PDZ domain inhibitors have been described in the literature (10,11,16,17,35,36). Most of these have been designed on the basis of selected scaffolds rather than high-throughput screening of compound libraries including inhibitors of, e.g., dishevelled [affinity up to~10 ÎźM (10, 36)] and NHERF1 (affinity~15 ÎźM) (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few compounds have been identified, and in general they display low affinities for their target (>100 ÎźM) (10,11,(16)(17)(18). Here we report the identification of a nonpeptide small-molecule inhibitor (FSC231) of the PICK1 PDZ domain.…”
mentioning
confidence: 95%
“…The core scaffolds that target Bcl-X L -Bad, gp41, Mdm2-p53, XIAP-caspase-9, CD4-MHC II [337] and IL-2-IL-2R interactions [338,339] are overwhelmingly hydrophobic. In contrast, such interactions as Ras-effector and PTEN-MAGI3 [340,341] are mainly mediated by -strands hydrogen bonds and electrostatic attractions, and those targets have unavoidably experienced obstacles to achieve low IC 50 . These facts imply the poorly-understood but pivotal roles of entropy and desolvation effects that trigger protein-protein association.…”
Section: Towards Potent Ppi Inhibitorsmentioning
confidence: 99%